Feminist Re-writing in Angela Carter’s The Bloody Chamber - P.Priyanka, P.Priyanka (International Journal of English Literature and Social Sciences (IJELS), 2019)
The Bloody Chamber is the first well received work of Angela Carter. Angela Carter, the feminist writer of twentieth century presents stories free from patriarchal influence. She has re-written the popular folk and fairy tales like Red Riding Hood, Blue Beard, Sleeping Beauty in feminist perspective. In the course of re-writing the tales, she alters the original plot to give an unexpected end. The Bloody Chamber and other short stories published in 1979 presents the modern feminist want for a strong woman in literature. She has employed magical realism in her stories to give a realistic view of the modern world along with magical elements. She has undermined the gender roles of masculinity and femininity. Blue Beard is a folk tale written by Charles Perrault in which a man named Blue Beard murders his wives. This plot is taken by Angela Carter and she has created strong, independent and witty women characters. This paper discuses the effect of patriarchal narration and fruitful result when the phallocentrism is removed from the plot.